Polymerase Chain Reaction Detection of Enterotoxins Genes in Coagulase-Negative Staphylococci Isolated from Brazilian Minas Cheese - Mores Rall, Vera Lucia [UNESP]; Sforcin, Jose Mauricio [UNESP]; Ramos de Deus, Maria Fernanda [UNESP]; de Sousa, Daniel Casaes [UNESP]; Camargo, Carlos Henrique [UNESP]; Godinho, Natalia Cristina [UNESP]; Galindo, Luciane Almeida [UNESP]; Siqueira Soares, Taissa Cook [UNESP]; Araujo, Joao Pessoa [UNESP] (Mary Ann Liebert, Inc., 2010)
For a long time, Staphylococcus aureus has been always thought to be the only pathogenic species among Staphylococcus, while coagulase-negative staphylococci (CNS) were classified as contaminant agents. However, molecular techniques have shown that these microorganisms also possess enterotoxin-encoding genes. The aim of this study was to analyze the frequency of genes for staphylococcal enterotoxins SEA, SEB, SEC, and SED in CNS strains isolated from Minas soft cheese and to assess the in vitro production of toxins. CNS were found in 65 (72.2%) samples of cheese: 23 were Staphylococcus saprophyticus, 16 Staphylococcus warneri, 10 Staphylococcus epidermidis, 9 Staphylococcus xylosus, 3 Staphylococcus haemolyticus, 2 Staphylococcus schleiferi subsp. schleiferi, and 1 each Staphylococcus capitis subsp. urealyticus and Staphylococcus caprae. Seventeen (26.2%) CNS strains had genes for enterotoxins, and sea was more frequently found (18.5%), followed by sec in three and seb in two strains, whereas the sed gene was not found. S. saprophyticus showed enterotoxin genes in 6 of 23 isolates, but only sea was observed. on the other hand, five strains of S. warneri showed the sea, seb, or sec gene. In spite of the presence of these enterotoxin genes, these strains did not produce enterotoxins in vitro. It is essential to understand the real role of CNS in food, and based on the presence of enterotoxin genes, CNS should not be ignored in epidemiological investigations of foodborne outbreaks.